Trypanosomatid parasites causing neglected diseases - Nussbaum, Kathrin; Honek, J.; Scheele, Catharina; Efferth, T. (Current medicinal chemistry, 2010)
Parasitic diseases such as Kala azar (visceral leishmaniasis), Chagas disease (American trypanosomiasis) and African sleeping sickness (human African trypanosomiasis) are affecting more than 27 million people worldwide. They are categorized amongst the most important neglected diseases causing approximately 150,000 deaths annually. As no vaccination is available, treatment is solely dependent on chemotherapeutic drugs. This review provides a comprehensive insight into the treatment of Kala azar, Chagas disease and African sleeping sickness. In addition to established drugs, novel small-molecule-based therapeutic approaches are discussed. Drugs currently used for the treatment of Kala azar include pentavalent antimonials, Amphotericin B, Miltefosine, and Paromomycin. Liposomal formulations such as AmBisome® provide promising alternatives. Furthermore, antiproliferative compounds might open new avenues in Kala azar treatment. Regarding Chagas disease, chemotherapy is based on two drugs, Nifurtimox and Benznidazole. However, sequencing of T. cruzi genome in the year 2005 raises a hope for new drug targets. Proteases, sterols and sialic acids are potential promising drug targets. Suramin, Pentamidine, Melarsoprol and Eflornithine are well-established drugs to treat African sleeping sickness. New treatment options include combination therapy of Eflornithine and Nifurtimox, a Chagas disease therapeutic. However, all approved chemotherapeutic compounds for trypanosomatid diseases suffer from high toxicity. Further, increasing resistance limits their efficacy and compliance.
Gesehen am 03.07.2023